Combination of carbohydrases and essential oils improve dietary performance of feedlot steers on a high-energy diet - Abreu, Jorge Augusto Dias da Costa; Neumann, Mikael; Paris, Wagner; Souza, André Martins de; Delai Vigne, Gabriela Letícia; Almeida, Eduardo Rodrigues de; Cristo, Fernando Braga; Sidor, Fernando de Souza (Semina: Ciências Agrárias, 2022)
Essential oils and enzymes are alternatives to feed additives for ruminants that aim to replace the use of ionophores and improve animal performance, but their mechanisms of action are different. Therefore, the present study aimed to verify if there is a synergistic effect in the combined use of enzymes carbohydrates and essential oils on the performance, ingestive behavior and carcass traits of steers fed a high-energy diet. During the finishing period of 78 days, 40 steers were assigned to four treatments: CON- control; ENZ- enzymatic complex; EO- essential oil blend; ENZ+EO - enzymatic complex combined with essential oil blend. Regardless of the feedlot periods, the ENZ+EO treatment caused a reduction in the dry matter intake (12.48%) compared to the control. The ENZ+EO treatment resulted in the lowest mean fecal output and, consequently, the highest dry matter digestibility (DMD) and starch digestibility (SD), compared to the other treatments. Animals that received EO and ENZ+EO in the diet spent more time in feeding. As for the number of times animals visited the feeding trough, the highest values were presented by the animals in the EO, ENZ and ENZ+EO treatments. For the carcass parameters, only the subcutaneous fat thickness on the rib was significantly different between treatments, with the highest values obtained by adding EO and ENZ+EO (8.80 and 8.10 mm respectively). Thus, the combination of carbohydrate enzymes and essential oils proved to be synergistically beneficial in relation to better use of nutrients and productive performance of feedlot steers.